2004
DOI: 10.1038/sj.gt.3302418
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with plasmid DNA encoding mycobacterial hsp65 in association with chemotherapy is a more rapid and efficient form of treatment for tuberculosis in mice

Abstract: Tuberculosis (TB) remains a threat for public health, killing around 3 million people a year. Despite the fact that most cases can be cured with antibiotics, the treatment is long and patients relapse if chemotherapy is not continued for at least 6 months. Thus, a better characterization of the working principles of the immune system in TB and identification of new immunotherapeutic products for the development of shorter regimens of treatment are essential to achieve an effective management of this disease. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 33 publications
4
68
0
6
Order By: Relevance
“…24,25 This vaccine also induced upregulation of MHC class I and class II molecules on macrophages. 26,27 Moreover, different groups have found that mycobacterial hsp65 gene transfer can elicit a profound antitumoral effect. 28,29 The transfection of J774 histiocytic sarcoma cells with the hsp65 gene resulted in reduced tumor development, and immunization with hsp65-transfected sarcoma cells in mice was protective against challenge with unmodified parental tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 This vaccine also induced upregulation of MHC class I and class II molecules on macrophages. 26,27 Moreover, different groups have found that mycobacterial hsp65 gene transfer can elicit a profound antitumoral effect. 28,29 The transfection of J774 histiocytic sarcoma cells with the hsp65 gene resulted in reduced tumor development, and immunization with hsp65-transfected sarcoma cells in mice was protective against challenge with unmodified parental tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, using a TB model that classically induces a Th1 pattern, mice immunized with DNAhsp65 showed increases of protective cytokines, IFN-␥ and IL-12. 3,32 Interestingly, in this work we showed that besides the strong Th2 polarization induced by S. mansoni eggs, DNA-hsp65 was able to maintain increased levels of IFN-␥ and IL-12 while simultaneously decreasing the release of Th2-related cytokines (Figure 4). This polarization of the immune response induced by DNA treatment could be associated with the size of lung lesions observed (Figure 1), as well as with differential activation of macrophages in the site of granulomas (Figure 3).…”
Section: Discussionmentioning
confidence: 62%
“…Prophylactic DNA vaccines expressing various M. tuberculosis antigens, including Ag85A, Ag85B, MTP-64, ESAT-6, 65-kDa heat-shock protein and PstS-3, were found to be effective at limiting the growth of M. tuberculosis in heavily infected mice. [11][12][13][14] After the completion of chemotherapy in mice infected with M. tuberculosis intravenously, vaccination with plasmid DNA expressing 65-kDa heat-shock protein was effective in preventing reactivation. 14 Ag85A DNA vaccine, when simultaneously administered with chemotherapy, could effectively prevent reactivation of aerogenically transmitted M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%